1991
DOI: 10.1111/j.1365-2621.1991.tb08034.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Sugars and Organic Acids in Cheddar Cheese by High‐Performance Liquid Chromatography

Abstract: In a simple, rapid isocratic HPLC method sugars and organic acids were separated on an Aminex HPX-87 column in the H+ form and detected using ultraviolet and refractive index detectors in series. Sugars (lactose, glucose and galactose) and acids (erotic, citric, pyruvic, lactic, uric, formic, acetic, propionic, butyric and hippuric) were identified by retention times. This method affords a simple technique for monitoring starter culture activity and following quality changes during cheese maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 10 publications
3
63
0
1
Order By: Relevance
“…The ratio of lactic acid produced is essential for assuring the good quality and proper ripening process of cheeses (Califano and Bevilacqua, 2000). An analogous trend was observed during the ripening of the different types of cheese (Bouzas et al, 1991;Zeppa et al, 2001;Akalin et al, 2002).…”
Section: Organic Acidsmentioning
confidence: 66%
See 2 more Smart Citations
“…The ratio of lactic acid produced is essential for assuring the good quality and proper ripening process of cheeses (Califano and Bevilacqua, 2000). An analogous trend was observed during the ripening of the different types of cheese (Bouzas et al, 1991;Zeppa et al, 2001;Akalin et al, 2002).…”
Section: Organic Acidsmentioning
confidence: 66%
“…The reason for high concentrations of oratic acid in cheese could be attributed to non starter microbial enzymes and rennet activity which facilitate more extensive biochemical reactions (Lues and Botha, 1998). Bouzas et al (1991), Akalin et al (2002), Manolaki et al (2006), Park and Lee (2006) working with different cheese types reported variable results for oratic acid.…”
Section: Organic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactose, lactic acid and ion contents of the samples were determined by high performance liquid chromatography (HPLC) [1,11]. Total solids were determined according to the 4A/1982 IDF standard.…”
Section: Methodsmentioning
confidence: 99%
“…The lactose, galactose, citric acid, lactic acid, acetic acid, propionic acid and butyric acid contents of the cheeses were determined according to the HPLC method described by Bouzas et al [6] for the simultaneous analysis of sugars and organic acids in cheese, using an Aminex HPX-87 column (Bio-Rad Laboratories, Richmond, CA, USA) and ultraviolet and refractive index detectors in series. Samples for HPLC analysis were prepared according to Bouzas et al [6]. Twenty-five millilitres of 0.009 N H 2 SO 4 were added to 5 g of ground cheese and extracted for 1 h while mixing using a magnetic stirrer.…”
Section: Chemical Analysesmentioning
confidence: 99%